Studi Literatur: Efek Pemberian Obat Herbal terhadap Penderita COVID-19 - Cyntia Bella Anggraini; Dewi Mayasari; Yurika Sastyarina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
COVID-19 is a disease that has never been identified in the human body before and is highly contagious. Coronavirus Disease 2019 (COVID-19) is caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Due to the high number of casualties due to COVID-19, many ways have been done to treat the outbreak of this virus. One of them is the use of herbal medicines from plants that are believed to cure people with COVID-19. This study aims to describe the impact of herbal medicine on patients with Covid-19. Literature search using PubMed, ScienceDirect and Google Scholar. Literature search strategy using keywords Traditional Chinese medicine, Chinese medicine, Chinese herbal medicine, COVID-19, new coronavirus pneumonia, SARS-CoV-2. The results obtained, namely from 10 literature show that herbal treatment can reduce symptoms of Covid-19 and boost the immune system. The use of herbal medicines for COVID-19 needs to be considered carefully to support the limited scientific data.